Exploration of Electrical, Thermal, and Mechanical Properties of Phaseolus vulgaris Fiber/Unsaturated Polyester Resin Composite Filled with Nano–SiO2 - B. Gurukarthik Babu; D. Prince Winston; P. V. Aravind Bhaskar; R. Baskaran; P. Narayanasamy (Journal of Natural Fibers, 2021)
In this study, the electrical, thermal, and mechanical properties of hybrid natural fiber composite are taken under consideration. Fly ash waste is used as the filler material. Unsaturated polyester resin is used as the matrix material to bind the composite. Alkali-treated Phaseolus vulgaris fiber (PVF) (5% NaOH for 45 min) is taken as the primary filler. Nanosilica synthesized is added to the composite samples at a constant percentage (1%). Samples of various weight percentages are prepared (2%, 4%, 6%, 8%, and 10% of PVF) and studied. Dielectric strength test for electrical property, thermal conductivity test for the thermal property, mechanical tests like tensile strength, Brinell hardness, Izod impact tests, and water absorption test are also taken under consideration. The composite showed a regular increasing trend in mechanical and electrical properties with varying weight percentages until 6% PVF; afterward, a decreasing trend in the mechanical and electrical properties of the composite was found with greater weight percentages. Whereas for thermal conductivity and water absorption tests, the results showed a regular decreasing trend until 6% PVF; afterward an increasing trend was found. It is found that the composite of 6% PVF and 1% SiO2 shows better electrical, thermal, and mechanical properties.